Challenging Achievement of Bidirectional Block After Linear Ablation Affects the Rhythm Outcome in Patients With Persistent Atrial Fibrillation. Issue 10 (10th October 2016) - Kim, Tae‐Hoon; Park, Junbeom; Uhm, Jae‐Sun; Kim, Jong‐Youn; Joung, Boyoung; Lee, Moon‐Hyoung; Pak, Hui‐Nam
Abstract : Background: It is not clear whether bidirectional block (BDB) of linear ablations reduces atrial fibrillation (AF) recurrence after radiofrequency catheter ablation. We hypothesized that BDB of linear ablation has prognostic significance after radiofrequency catheter ablation for persistent AF. Methods and Results: Among 1793 consecutive patients in the Yonsei AF ablation cohort, this observational cohort study included 398 patients with persistent AF (75.6% male; age, 59.8±10.3 years) who underwent catheter ablation with a consistent ablation protocol of the Dallas lesion set: circumferential pulmonary vein isolation; cavotricuspid isthmus ablation (CTI); roof line (RL); posterior‐inferior line (PIL); and anterior line (AL). BDB rates of de novo ablation lines were 100% in circumferential pulmonary vein isolation, 100% in CTI, 84.7% in RL, 44.7% in PIL, and 63.6% in AL. During 29.0±18.4 months of follow‐up, 31.7% (126/398) of the patients showed clinical recurrence. Left atrial posterior wall (LAPW) isolation (BDBs of RL and PIL) was independently associated with lower clinical AF/atrial tachycardia recurrence (hazard ratio, 0.68; 95% CI, 0.47–0.98; P =0.041; log‐rank, P =0.017), whereas BDBs of RL or AL were not (log‐rank, P =0.178 for RL; P =0.764 for AL). Among 52 patients who underwent repeat procedures (23.0±16.1 months after de novo procedure), the BDB maintenance rates for CTI, RL, PIL, and AL were 94.2% (49 of 52), 63.5% (33 of 47), 62.1% (18 of 29), and 61.8% (21 of 34), respectively. Conclusions: Although PIL crosses the esophageal contact area, LAPW isolation is important for better clinical outcome in catheter ablation with a linear ablation strategy for patients with persistent AF.